Probing helium nano-bubble formation in tungsten with grazing incidence small angle x-ray scattering. (11th March 2015) - Thompson, M.; Kluth, P.; Doerner, R.P.; Kirby, N.; Corr, C.
Abstract: Helium nano-bubble formation in plasma facing materials has emerged as a major concern for the next-step fusion experiment ITER, where helium plasmas will be used during the tokamak's start-up phase. Here, we demonstrate that grazing incidence small-angle x-ray scattering is a powerful technique for the analysis of helium nano-bubble formation in tungsten. We measured helium bubbles with sizes between 1.5–2.5 nm in tungsten exposed to helium plasma at 700 °C, where a smaller number of larger bubbles were also observed. Depth distributions can be estimated by taking successive measurements across a range of x-ray incidence angles. Compared with traditional approaches in the field, such as transmission electron microscopy, this technique provides information across a much larger volume with high statistical precision, whilst also being non-destructive.